Effects of nitrogen source and effective micro-organisms on vegetative growth of shrubs of selected grapefruit (Citrus paradisi Macf) cultivars - Elkashif, Mohamed E; Suliman, Suhair A; Elamin, Osman M. (Gezira Journal of Agricultural Science; Vol 14 No 1 (2016), 2016)
Grapefruit ( Citrus Paradisi Macf . ) is one of the most important citrus fruits in the Sudan. It can be successfully grown throughout the country where there are suitable soils and sufficient water to sustain tree growth. The objectives of this study were to find out the effects of different nitrogen sources, effective microorganisms (EM) and their combinations on the vegetative growth of shrubs of selected grapefruit cultivars. A field experiment was carried out at Umbarona, Wad Medani, Gezira State, Sudan, latitude 14.38 N, longitude 33.48 E and altitude 409 masl, in June 2012. Treatments consisted of three grapefruit cultivars: Marsh Seedless, Red Blush and Shamber. Fertilizer treatments were urea (100%), chicken manure (100%), urea with chicken manure (50% each), urea with EM, chicken manure with EM, urea (50%)+ chicken manure (50%)+ EM and unfertilized control. All fertilizer treatments were applied at the rate of 43 kg N/ha. Treatments were arranged in a split- plot design with two replicates. Grapefruit cultivars were allotted to the main plots and fertilizer treatments to the sub-plots. Data were collected on plant height (cm), stem diameter (cm), number of new branches, length of new branches (cm) and diameter of new branches (cm). Results showed that Marsh Seedless cultivar had the most vigorous vegetative growth compared to the other two cultivars. The results showed that the combination of urea, chicken manure and EM significantly gave the highest vegetative growth values, followed by chicken manure with EM, urea with chicken manure, urea with EM, urea alone, chicken manure alone and the least values of growth parameters were recorded for the unfertilized control. It is recommended to grow Marsh Seedless grapefruit cultivar and fertilize it with a combination of urea, chicken manure and EM.         يعتبر القريب فروت من أهم ثمار الحمضيات في السودان ويمكن زراعته بنجاح في جميع أنحاء البلاد حيثما توفرت التربة المناسبة والمياه الكافية لنمو الأشجار. أجريت تجربة حقلية في ام بارونة، واد مدنى ولاية الجزيرة، السودان. تهدف هذه التجربة لمعرفة تأثير مصادر النتروجين المختلفة والكائنات الحية الدقيقة الفعالة ومزجها مع بعضها البعض على النمو الخضري لشجيرات أصناف منتخبة من القريب فروت. تضمنت المعاملات ثلاثة أصناف من القريب فروت وهي مارش  ورد بلش وشامبر وسبعة معاملات أسمدة وهي  اليوريا، وزرق الدواجن، يوريا مع زرق الدواجن، يوريا مع الكائنات الحية الدقيقة الفعالة، زرق الدواجن مع الكائنات الحية الدقيقة الفعالة، يوريا مع زرق الدواجن مع الكائنات الحية الدقيقة الفعالة والشاهد. تمت إضافة الأسمدة لكل المعاملات بمعدل 43 كجم نتروجين للهكتار. صممت التجارب بطريقة القطع المنشقة بحيث كانت أصناف القريب فروت هي القطع الرئيسة ومعاملات النتروجين هي القطع الثانوية. جمعت بيانات عن طول النبات (سم) وقطر الساق (سم) وعدد الأفرع الجديدة وطول الفرع (سم) وقطر الفرع (سم). أوضحت النتائج أن الصنف مارش أعطى أعلى نمو خضري مقارنة بالصنفين رد بلش وشامبر. الخليط بين سماد اليوريا وزرق الدواجن و الكائنات الحية الدقيقة الفعالة  أعطت أعلى معدل للنمو الخضري ويليه زرق الدواجن والكائنات الحية الدقيقة الفعالة ثم اليوريا والكائنات الحية الدقيقة الفعالة ثم اليوريا وزرق الدواجن ثم زرق الدواجن لوحده ثم اليوريا لوحده وأدنى معدلات  النمو كانت في الشاهد .  يوصى بزراعة الصنف قريب فروت مارش وتسميده بخليط من اليوريا وزرق الدواجن والكائنات الحية الدقيقة الفعالة.